Beyond visualization : productivity, complexity, and information overload - Maples, Creve (O'Reilly, 2011)
"We will discuss the impact of the information explosion, the effectiveness of current technological directions, and explore the success that new perception-based, human-computer interfaces provide in analyzing and understanding complex data. Real examples will be used to illustrate that effective man-machine environments are essential in productively dealing with multi-dimensional information."--Resource description page.